The interplay of organizational citizenship behaviour, innovative work behavior and organizational innovative culture in predicting employee performance in the automotive industry - J, Saranya; Anbu , A (International Journal of Management and Sustainability, 2025)
Employee performance (EP) is of the highest priority as it has a direct impact on organization's reputation and production efficiency. The purpose of this investigation is to find out the relationship between organizational innovation culture (OIC), organizational citizenship behavior (OCB), and innovative work behavior (IWB) driven by EP. A purposive sampling approach was employed to identify participants who exhibited specific attributes that were pertinent to the research objectives. A structured questionnaire was sent using Google Forms and hypotheses testing were employed to identify the results. Applications such as IBM SPSS 25 were used to assess the questionnaire's validity and reliability, and AMOS 21 was used to test the hypotheses. The results indicate that the automotive industry's employees exhibit a high level of OIC and OCB which is mediated by IWB and has an impact on their performance. The results indicate that the automotive industry's employees exhibit a high level of OIC, OCB and IWB and have a significant impact on their performance. Practical Implications: Organizations can establish a performance-driven work environment by encouraging employees to grow beyond their formal positions which can result in long-term performance changes thereby establishing a resilient workforce that is ready to meet future challenges.